Genetic Diversity of Trichoderma and Hypocrea lixii Iraqi Strains by Using Random Amplified Polymorphic DNA (RAPD) Technique - Handel, Israa Malallah (Iraqi Journal of Science, 2023)
As the diversity and characteristics of Trichoderma species are difficult to determine using morphological methods, henceforth molecular tools are crucial. This study utilized random amplified polymorphic DNA (RAPD) technique to investigate the genetic diversity of Trichoderma with sexual phase Hypocrea and to identify similarities and differences in the phylogenetic tree. Nine Iraqi Trichoderma strains (four strains of T. atroviride, one strain of Hypocrea lixii, two strains of T. gamsii and two strains of T. longibriantium) were examined in this research. The genomic DNA of each species was extracted and amplified with each of the five primers. 197 bands were obtained by using five oligodeoxynucleotide primers of which 98.47% were polymorphic and about 1.52% were monomorphic. When primers OPA4, OPA8, and OPA10 were used, the genetic variability was about 100%. Whereas, after using primers OPA7 and OPA5, the obtained genetic variability was 95.7% and 92.6% respectively. Gel images of the RAPD were processed with photo-cap program which detected the bands of isolates based on the ladder. The detected bands were then clustered based on the Jaccard method in Past software that showed T. atroviride, T. gamsii, Hypocrea lixii, and T. longibrachiatum isolates were grouped as clades and lineages. Although all strains belonged to the same species and group in one clade, they differed in size and number of bands. The Jaccard cluster analysis showed that the three isolates of T. atroviride were closely related to each other, while the four isolates of T. atroviride in one cluster were same as Hypocrea lixii, the isolates of T. gamsii and two strains of T. longibrachiatum formed one cluster. Thus, the high reliability of RAPD markers could be applied to identify Trichoderma species and create genetic maps instead of other DNA-based methods which are not only costly but time-consuming too.